Gavrilo Princip and Street art: пример идеолошке трансформације - Lazarević Radak, Sanja (Serbian political thought, 2024)
Despite being instrumentalized through written narratives and the official history, both in the Kingdom of Yugoslavia and in the Socialist Federal Republic of Yugoslavia, Gavrilo Princip, in Serbia, along with the official, historical role becomes a subcultural hero, as evidenced by the continuous use of his image in street art. In order to understand the use of his biography in popular culture and in the public space, the analysis included murals in which Princip is represented as: 1. Martyr; 2. Moral winner and 3. Protector of football fan subculture. Analysis shows that all three figures remain interdependent, so the contents of one are present in the other, thus forming a complex representation of resistance that transcends ideological, political and cultural boundaries. In this sense, the representations of the "moral winner" and the "protector of the fans" can be understood as subvariants of the notions of heroism and martyrdom belonging to the broader political context. Relying on the concepts of Girardet golden age and the Laclau empty signifier, the author interprets the visual adaptations of Gavrilo Princip’s character to different chronological and cultural circumstances.